Molecular Subtypes of Breast Cancer Patients According to St Gallen Classification (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Introduction: Breast cancer is a common malignancy among female in Bangladesh.But its molecular subtypes are not evaluated due to lack of expert investigationsupport. So objectives of the present study are to evaluate the molecular subtypesof breast cancer patients according to St Gallen classification in our contest.Materials and methods: It is retrospective study done among histopathologicallyproved 40 breast cancer patients visiting Medical Oncology and Radiotherapydepartment of Chattogram Maa-O-Shishu Hospital. Molecular subtypes wasevaluated by immunohistochemistry according to St Gallen Classification.Results: In this study a total of 40 cases of invasive female breast cancers wereincluded. Age of the patients ranged from 31-62 years, with a mean age of 41 ±13.5 years. ER expression was seen in 60% and PR in 55% of cases and Her-2/neupositivity in 16%. Majority (52.5%) of the tumors were located in the left breast. Thepercentage of ER but not PR positivity increased with age, though this differencewas not statistically significant. Majority of the cases were diagnosed at stage IIwith a percentage of 42.5%. Stage II tumors showed more ER and PR positivity.Among all 57.9% of ER positive and 49.5% of PR positive tumors were present while72.2% of tumors were negative for Her-2/neu. The triple-negative breast tumorswere more commonly found at grade 2. Regarding luminal status 14(35%) wasLuminal A, 5(12.5%) was Luminal B, 9(22.5%) was TNBC and 12(30%) was HER 2positive.Conclusion: In this study luminal A was the commonest molecular subtypes. LuminalA subtypes tumors had a long term risk of distant matastatic disease which can bereduced by hormonal treatment.Chatt Maa Shi Hosp Med Coll J; Vol.19 (1); January 2020; Page 55-58